The Little Green Data Book 2012 - World Bank (Washington, DC, 2013)
This year's edition of the little green data book includes a focus story on oceans and its ecosystem services, as well as estimates of global marine fisheries wealth accounts, a first step in capturing the value of this important resource stock. A new set of ocean-related indicators are also introduced, highlighting the role of oceans in economic development and providing policy makers the information to make better decisions for the sustainable management of oceans. These and other related data are freely available online at data.worldbank.org as part of the World Bank's open data initiative. For more than a decade, the little green data book has served as a knowledge resource that aids policy makers in using environmental data more effectively to support priority-setting and improve development outcomes. It is the result of close collaboration between the Development Data Group of the Development Economics Vice Presidency and the Environment Department of the Sustainable Development Vice Presidency of the World Bank.